Comparing the usability and users acceptance of open sources Learning Management System (LMS) - Sim, Yue Hock; Omar, Ridha; Mahmud, Murni (2015)
- Learning Management System (LMS) or online learning portal has become an electronic learning and communicating ways for many higher education institutions in Malaysia. The use of eLearning has increased in this few years and open source learning management systems have become a popular choice for these higher education institutions in Malaysia. Ensuring the LMS usability is an important factor that can affect the overall acceptance and success of the platforms. Therefore, in this paper the authors will evaluate the usability factor of three open source LMS platforms (Moodle, ILIAS and Atutor) on desktop/ pc environment; and the comparative evaluation results are then presented.